A Critical Look Into the Role of Public Enterprises - Bautista, Victoria A. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The growth of public enterprises outside of centrally-planned economies has become prominent in recent years, particularly in the case of the Third World. Considering the rise of public enterprises, this paper examines the role played by these entities in Philippine development. Public enterprises refer to corporations which are wholly-owned or controlled by the government. There are several reasons for their establishment. First, public enterprises are seen as entities that forge nationalism by assuring control of the economy by Filipinos. Second, the urgent need for development requires the immediate establishment of government corporations to demonstrate economic viability. Third, because of “barriers to entry”, it is only the government that could exploit certain opportunities. Fourth, the direct role of government in business is needed for “public trust and interest” reasons. Lastly, government corporations are believed to aid business in financial distress. However, the major criticism leveled against these enterprises is that they have only served to promote local and foreign monopolistic interests. By focusing on four case studies, the paper shows how an alliance has been actually maintained between these public enterprises and local monopoly capitalists in order to protect private interests. Initial findings of the study show that public enterprises have promoted monopolistic capitalistic intent of domestic and foreign entrepreneurs. Private interest is assured when monopoly capitalists assume key positions in public enterprises and other government entities because of their direct access to planning and implementing structures. Furthermore, the paper argues that public policies should be geared towards self-reliance rather than dependence on foreign entrepreneurs because self-reliant development inspires nationals to be more creative and become directly responsible in defining the activities they pursue.
Keywords: public enterprises, Third World, Philippine development, economy, public policies, monopoly capitalist